Global asymptotic stability for a distributed delay differential-difference system of a Kermack-McKendrick SIR model - Adimy, Mostafa; Chekroun, Abdennasser; Kuniya, Toshikazu (Applicable analysis, 2023)
We investigate a system of distributed delay differential-difference equations describing an epidemic model of susceptible, infected, recovered and temporary protected population dynamics. A nonlocal term (distributed delay) appears in this model to describe the temporary protection period of the susceptible individuals. We investigate the mathematical properties of the model. We obtain the global asymptotic stability of the two steady states: disease-free and endemic. We construct appropriate Lyapunov functionals where the basic reproduction number appears as a threshold for the global asymptotic behavior of the solution between disease extinction and persistence.